2005
DOI: 10.1521/scpq.2005.20.3.224
|View full text |Cite
|
Sign up to set email alerts
|

The 50th anniversary of the Thayer Conference: Historical perspectives and accomplishments.

Abstract: Information from several historical sources provides a clearer understanding of the Thayer Conference, including little-known background information. Changes in school psychology since the conference are described through comparisons of the field at the time of the conference and at present. Major recommendations and expectations emanating from the Thayer Conference are reviewed against subsequent developments in the field. Most of the recommendations for the future of the field have been accomplished. Those i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…Discussions regarding the role and function of school psychologists in addressing the mental health needs of students have taken place in the literature (e.g., Bardon, 1968; Brown & Bolen, 2003; Kramer & Epps, 1991; Meyers & Swerdlik, 2003; Semrud‐Clikeman, 2005; Shapiro, 1991; Tharinger, Pryzwansky, & Miller, 2008) and at conferences (e.g., 1954 Thayer Convention; Fagan, 2005; Semrud‐Clikeman, 2005) for more than 50 years. Few articles, however, have addressed the training of school psychologists who plan to provide mental health services to students or the ethical issues that may occur during the delivery of school‐based mental health services (SMHS).…”
mentioning
confidence: 99%
“…Discussions regarding the role and function of school psychologists in addressing the mental health needs of students have taken place in the literature (e.g., Bardon, 1968; Brown & Bolen, 2003; Kramer & Epps, 1991; Meyers & Swerdlik, 2003; Semrud‐Clikeman, 2005; Shapiro, 1991; Tharinger, Pryzwansky, & Miller, 2008) and at conferences (e.g., 1954 Thayer Convention; Fagan, 2005; Semrud‐Clikeman, 2005) for more than 50 years. Few articles, however, have addressed the training of school psychologists who plan to provide mental health services to students or the ethical issues that may occur during the delivery of school‐based mental health services (SMHS).…”
mentioning
confidence: 99%
“…Ultimately, conference attendees proposed dual-level credentialing in which doctoral-1 The division's official title was subsequently changed to the Division of School Psychology in the late 1960s, broadening the definition of the discipline beyond the school setting (Fagan, 2000). 2 Cutts' description of school psychologists was masculine even though Fagan (2005a) reported that 55% to 60% of the school psychologists in 1955 were women. This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Why Division 16 Should Embrace a Broad Ecological Role For S...mentioning
confidence: 99%
“…The resulting standards for credentialing borrowed heavily from the medical model of psychiatry, and because school psychology already accessed credentialing through state education agencies, Division 16 was only minimally involved in this effort. Instead, within 3 years, Division 16 leaders sought and received support from APA and the U.S. Public Health Service to convene a similar conference on standards for training of public-school psychologists (Fagan, 2005a). The division’s Thayer Conference met for 3 days in August 1954 in West Point, New York.…”
Section: Why Division 16 Should Embrace a Broad Ecological Role For S...mentioning
confidence: 99%
See 1 more Smart Citation
“…I was delighted when Rik Carl D’Amato, Editor-in-Chief of School Psychology Quarterly, asked me to review an earlier draft of Thomas Fagan’s manuscript on the 50th anniversary of the Thayer Conference (Fagan, this issue). I have an immense respect for Fagan’s knowledge of school psychology.…”
mentioning
confidence: 99%